Dental implant surface morphology, chemical composition, and topography following double wavelength (2780/940 nm) laser irradiation. An in vitro study. Issue 1 (1st January 2023) - Fahlstedt, Peter; Wennerberg, Ann; Bunæs, Dagmar F.; Lie, Stein A.; Leknes, Knut N.
Abstract: Objective: The aim of this in vitro study was to evaluate morphology alterations, chemical composition, and topography of moderately rough dental implants following double‐wavelength laser irradiation. Material and Methods: Commercial‐grade titanium dental implants representing different surface characteristics (Osseospeed [OS], TiUnite [TiU], and Roxolid SLActive [RS]) were used. Laser irradiation was performed using a computer‐controlled robotic device with calibrated energy/power settings and deionized water spray. Micro‐, nano‐morphology surface alterations, chemical composition, and surface topography ( S a, S ds, S dr ) in the test group (laser plus water), control group A (water only), and control group B (no treatment) were analyzed using scanning electron microscopy (SEM), energy‐dispersive X‐ray analysis (EDX), and white light laser profilometer (Interferometry). Results: SEM‐evaluation revealed minor between‐group differences in micro‐ and nano‐morphology within each implant system. Significant overall differences in surface element content were observed between the test and control group B for all implant systems ( p < .05). For the test compared with control group B, statistically significantly higher oxygen content was detected for OS and RS ( p < .05), a corresponding significant difference was detected for carbon for TiU ( p < .05). For RS, a significantly lower content of titanium and zirconium was detected within the test group ( p < .05). A significant difference in topography between test and control group B was observed for OS ( S a : p = .039 and S dr : p = .041) with the highest roughness value for control group B. Conclusions: Altered chemical composition and surface topography were observed for all implant surfaces compared with untreated control following double wavelength laser irradiation. A clinical evaluation of the impact of the altered surface composition following double wavelength laser irradiation on the ability to reosseointegrate appears warranted.